Risk Management of Preventing Money Laundering and Terrorist Financing (The Journal of Forensic Accounting Profession, 2023)
Aware of the danger that the risk of money laundering and terroist financing has on the whole society, and with the aim of increasing awareness of the effective fight against the same risk in Bosnia and Herzegovina (BiH), the paper deals with the research of mechanisms for managing the risk of money laundering and terrorist financing activities. The research of this work will be focused on determining the degree of application of the requirements of the legislative and institutional framework for the fight against money laundering and terrorist financing by those obliged to apply law. Also, the paper points to the cooperation of state institutions with entities of the BiH, and examines the degree of compliance of the BiH system with international standards related to the fight against money laundering and terrorist financing. In order to assess the management of this risk as efficiently as possible, the paper will cover financial and non-financial money transfer systems, and indicate the level of measures taken in this fight by the competent institutions. For the purposes of research in the paper, the data published by the competent institutions through their reports/publications will be used, with a special focus on the data published by the Banking Agency of the Federation of Bosnia and Herzegovina as the legal entity that reported the largest number of suspicious transactions in the analyzed period. The results of the research indicate that there is no concern regarding the management of the risks of money laundering and terrorist financing in BiH, and that the risk can be quantified in the category of moderate risk.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2022-0007, pod licencom CC BY-NC-ND 4.0)
Keywords: Risk; Money Laundering; Terrorist Financing; Suspicious Transactions; SIPA Financial Intelligence Department